Gender, Care and Migration in East Asia (Series in Asian Labor and Welfare Policies, 2018)
This collection provides a comparative analysis of care arrangements in relation to issues of gender and transnational migration, social policy and labour migration in East Asia. Bridging the key topics of migration and gendered cared work through cross country comparisons, it examines how care work and welfare arrangements have been shaped by national and global forces against the backdrop of changing gender relationships, the rise of female labour force participation, low fertility rates and population aging in East Asia. It particularly addresses the 'feminization of migration' which is a salient feature of migration in Asia today as more women from developing countries undertake domestic work and care work in Japan, Taiwan, South Korea and Hong Kong. Addressing the issue of care in relation to employment, care and migration regimes in East Asia and the interaction among welfare regimes, labour markets and work-care balance, this collection provides an up-to-date assessment of gendered transnational migration in the region and sheds light on local and transnational policies and practices which aim to improve the welfare of families and migrant workers.